Dimethyl‐methylphenyl copolysiloxanes by dimethylsilanolate‐initiated ring opening polymerization. Evidence for linearity of the resulting polymer structures. Issue 10 (27th March 2019) - Zlatanic, Alisa; Radojcic, Dragana; Wan, Xianmei; Messman, Jamie M.; Bowen, Daniel E.; Dvornic, Petar R.
ABSTRACT: Recently, we reported that dimethylsilanolate‐initiated anionic ring opening polymerization of dimethylsiloxy‐ and diphenylsiloxy‐cyclic siloxanes results in polymer chain branching by dimethylsilanolate‐induced cleavage of only one Si‐CAr side bond in diphenylsiloxy repeat units, leading to formation of "Ph‐T‐branches", and not extending to the cleavage of the second phenyl group. We attributed this behavior to electronic structures of the participating dimethylsiloxy‐, diphenylsiloxy and Ph‐T‐branch silicons and predicted that copolymers prepared by this synthetic route from dimethylsiloxy‐ and methylphenylsiloxy‐cyclics should not undergo branching at all but should have perfect linear chain configuration. Here, we describe results of a study of two such dimethylsilanolate‐initiated ring opening polymerizations of dimethylsiloxy‐ and methyphenylsiloxy‐cyclic tetramers and characterization of the resulting polymers by SEC‐MALS‐VIS, Mark‐Houwink‐Sakurada relationship and 29 Si NMR. The results obtained clearly confirmed our prediction of expected linearity of these polymer chains and also indicated that the resulting polymers were completely amorphous even at as low methylphenylsiloxy‐content as 3.9 mol %. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 1122–1129 Abstract : The results obtained clearly confirmed the prediction that in dramatic contrast to unavoidable chain branching in diphenysiloxy‐containing polymers, their methylphenyl‐containing derivatives should be all linear as well as completely amorphous even at as low methylphenylsiloxy‐content as 4 mol %. As a consequence, they now provide a clear explanation why these polymers are the polymers of choice for applications requiring pronounced material elasticity at very low temperatures.